Investigation on electrically-assisted diffusion bonding of Ti2AlNb alloy sheet by microstructural observation, mechanical tests and heat treatment. (5th November 2018) - Li, Xiao; Wang, Guofeng; Gu, Yibin; Li, Danfeng; Fang, Hui
Abstract: The process of diffusion bonding involves long time heating and needs bulky heating furnace. A long production cycle severely limits the commercial application on a large scale due to capital and energy costs. In an attempt to shorten the heating time in a cost-feasible manner, a novel electrically-assisted diffusion bonding (EADB) was proposed in this study. EADB is a result of applying electrically assisted concept to the conventional diffusion bonding process. Firstly, an EADB set-up was assembled to study the joining of Ti2 AlNb alloy sheet that is recently studied as an excellent high-temperature structural material. The temperature distributions under different electric current densities were experimentally studied and the Ti2 AlNb alloy sheets were successfully bonded without micro-cavity under 4.58 A/mm 2 . The microstructural evolution of EADB samples was discussed. Detour effect of electric current was found around the micro-cavity, which was determined by finite element analysis. Moreover, the mechanical tests of EADB samples showed that the highest shear strength was 587.24 MPa and the maximum hardness was 472.88 ± 6.36 HV/0.5/10. After that, heat treatment was used to homogenize the microstructures of EADB samples and the final samples showed basket-weave microstructures. Finally, comparisons with conventional processes were discussed in detail. Graphical abstract: Unlabelled Image Highlights: A novel diffusion bonding process assisted by electric current was presented and validated. Ti2 AlNb ally sheets were successfully bonded by a self-built experimental set-up. The maximum shear strength of bonding sample was 587.24 MPa and the highest hardness value was 472.88 ± 6.36 HV/0.5/10.